Mengendalikan Dopamine Detox - Hilwan Azhar Sukma (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to find out and learn about "Dopamine Detox" from the "1 Day of Success" youtube channel entitled "Control Yourself From All Addictions". In this study, a qualitative descriptive method was used, namely a method carried out by observing and noting techniques because the source of information was taken by listening to oral narratives. Dopamine detox can be a way to reduce or limit activities that are considered enjoyable but can have bad effects if done excessively. For example using gadgets, playing video games, or even eating snacks. The goal of a dopamine detox is to reduce addiction by changing bad habits to be more productive. Basically, dopamine cannot be eliminated from the body, but we can control dopamine levels by temporarily eliminating unhealthy entertainment and having high levels of dopamine. Dopamine levels that are too high can reduce concentration so that we lose focus. People who need a dopamine detox are people who are addicted to negative things, so the term dopamine detox actually doesn't really aim to reduce dopamine, but rather directs it so that dopamine can be produced in a way that is healthier, beneficial, not damaging to health, not disturbing productivity and does not make us lazy.